Mitochondrial dysfunction signatures in idiopathic primary male infertility: a validated proteomics-based diagnostic approach - Sawaid Kaiyal, Raneen; Mukherjee, Sromona D.; Panner Selvam, Manesh Kumar; Miller, Aaron W.; Vij, Sarah C.; Lundy, Scott D. (Frontiers in Reproductive Health, 2024)
Research questionMale infertility accounts for almost half of all infertility cases worldwide, with idiopathic male infertility accounting for up to 30% of the cases. Sperm proteomics has revealed critical molecular pathway changes in men with infertility. However, the sperm mitochondrial proteome remains poorly understood. We attempted to answer the following question: Do patients with idiopathic primary male infertility exhibit a proteomic signature associated with mitochondrial dysfunction that could be used as a target for future mechanistic investigations?DesignPatients with idiopathic primary infertility (20–40 years old) referred to the Cleveland Clinic between March 2012 and April 2014 were compared with fertile donor controls. Sperm proteins were analyzed using sodium dodecyl sulphate-polyacrylamide gel electrophoresis page (SDS-PAGE) and liquid chromatography-mass spectrometry (LC-MS), and differentially expressed proteins (DEPs) were identified based on significance test results and fold change thresholds. Protein expression was validated using western blotting.ResultsProteomic analysis of pooled samples from fertile donors (n = 5) and patients with idiopathic primary infertility (n = 5) identified 1,134 proteins, including 344 DEPs. Mitochondrial dysfunction topped the ingenuity toxicity list. Analysis of expression levels of three mitochondrial proteins known to combat oxidative stress revealed that peroxiredoxin-5 (PRDX5) and superoxide dismutase 2 (SOD2), but not glutathione disulphide reductase, were significantly decreased in patient samples compared with those in fertile-donor samples.ConclusionsThis study revealed an association of downregulated expression of PRDX5 and SOD2 in sperm samples of patients with idiopathic primary male infertility. Our results support future mechanistic studies and development of advanced diagnostic methods to better identify men with mitochondria-related male infertility.